Implementation of the Housing Stimulus Assistance Program Policy for Assistance in Providing Decent Housing in Munggut Village, Padas District, Ngawi Regency - Yusuf, Herviyanto (Civiliza Publishing, Indonesia., 2025)
The Self-Help Housing Stimulant Assistance (BSPS) is a government facility in the form of funds offered to low-income communities. Its development strength lies in building housing through the initiative and hard work of the community, both individually and collectively, including repairs, restoration, and construction of new homes and the environment. This study aims to determine the implementation of the Housing Stimulant Assistance Program policy in providing adequate housing in Munggut Village, Padas District, Ngawi Regency. This research method uses a qualitative descriptive approach. Data collection techniques through observation, interviews, and documentation, and analysis techniques using the concept of Miles Humberman. The results of this study indicate that the implementation of the Housing Stimulant Assistance Program policy in providing adequate housing in Munggut Village, Padas District, Ngawi Regency is not optimal. This includes a lack of participation and awareness, as well as a lack of knowledge about the Self-Help Housing Stimulant Assistance (BSPS) program. In addition, in the development stage, which should be carried out through mutual cooperation with predetermined groups, in reality it is still carried out individually. The researcher also observed that the implementers of this program lack firmness because they still allow the community to work individually and are apathetic towards it.